Equipping undergraduate medical and nursing students with elderly health care assessment skills at Makerere University, College of Health Sciences, Uganda - Noeline Nakasujja; Faith Nawagi; Blessed Tabitha Aujo; Aidah Ajambo (BMC Geriatrics, 2023)
Abstract Background Elderly health care training and aging science remain the least prioritized discipline of medical education in many African countries. With scant scientific evidence on elderly health care in low-income countries, coupled with limited exposure to elderly health care training, this project aimed to equip undergraduate health professional students with elderly health care assessment skills and research through an online course and a clinical placement. Methods Students (3rd year) underwent online elderly health care training through the Alison courses published by the Advanced Learning Academy in Ireland. The students were then subjected to an online exam with a pass mark of 80%. Students were also trained on standard elderly health care assessment tools through a one-day session. For practical skills on data collection, each student assessed 15 elderly patients at the Mulago National Referral Hospital Assessment Centre. All tools once filled in were assessed for completion. A one-day reflection session was held with students, faculty and the project leads to share findings from the various tools used to assess elderly individuals. The students shared their experiences and provided feedback on the online training as well as the hardships they may have experienced while administering the tools. A certificate of participation was provided to the students at the end of the project. Results All the students (10) gained knowledge on elderly assessment skills, the impact of aging on various body systems, and how to manage common occurrences among elderly individuals. The average score in the post-exam was 82% (standard deviation ± 2.01). All students (10) reported having had this as their first training on the assessment of functionality among elderly individuals. Conclusions The students gained knowledge of elderly health assessments as well as the impact of aging on various body systems. They also gained insight into how to care for the elderly holistically with an added understanding of how to manage spinal and traumatic brain injuries.